Pengaruh Air Limbah Tempe terhadap Pertumbuhan Kakao (Theobroma cacao L) - Nugroho, Setyo Andi; Wulandari, Uci Faridila; Fatimah, Titien; Novenda, Ika Lia (Agropross : National Conference Proceedings of Agriculture, 2023)
Cocoa plants have economic value and are a source of foreign exchange for the country. According to ICCO data for 2021, the total production of Indonesian cocoa plants for the last 5 years has decreased. The decline in Indonesia's cocoa production was caused by aging cocoa trees. The production of cocoa must pay attention to aspects of cultivation to increase the quality and quantity of production. Nurseries can affect further growth and produce maximum production. The aim of this study was to determine the effect of giving tempe wastewater on the growth of cocoa (Theobroma cacao L.). The research was conducted at the Saung of the Jember State Polytechnic, Sumbersari-Jember District, from September 2022 to January 2023. The study used a factorial randomized block design with 2 factors. The first factor is the composition of the topsoil planting medium: manure: sand which consists of 3 levels: 2:1:1 (A1), 1:2:1 (A2), 1:1:2 (A3). The second factor is tempe wastewater: EM4: Aquadest which consists of 3 levels, namely 300 ml: 100 ml: 600 ml (B1), 500 ml: 100 ml: 400 ml (B2), 600 ml: 100 ml: 300 ml (B3 ). The results of the research gave significantly different results for the parameter of stem diameter and significantly different for the parameter of plant height.